Poststructuralism and Representation - Thomassen, Lasse (Political studies review, 2017)
This article maps debates within poststructuralism, particularly poststructuralist political theory. I argue that the category, or question, of representation can make sense of theoretical and political debates within poststructuralism in general and poststructuralist political theory in particular. Poststructuralists criticise all forms of presence, whether the presence of the subject, identities or structures. Following poststructuralism, representation can no longer be seen as the reflection of a presence. However, while poststructuralists agree on the turn away from presence, they disagree where to turn and, specifically, on the role and nature of representation. They disagree whether representation is constitutive, and they disagree about how to relate to the hierarchy and violence which, they all agree, is a part of representation. The question of representation may not explain all divisions among poststructuralists, but the question of representation divides poststructuralism in so many ways that it makes sense to analyse the differences among them through the lens of representation. I first look at two issues central to poststructuralism: critique and how to relate to ‘the other’. In the second half of the article, I turn to look at three debates within poststructuralism: immanence versus transcendence, abundance versus lack, and autonomy versus hegemony.